Global systematic review of occupational health and safety outcomes among sanitation and hygiene workers - Tolera, Sina Temesgen; Temesgen, Shibiru; Mulat Endalew, Salie; Alamirew, Tamagnu Sintie; Temesgen, Liku Muche (Frontiers in Public Health, 2023)
Introduction: Sanitary workers are exposed to a variety of occupational hazards in a variety of working environments, which can result in occupational-related outcomes. As a result, the goal of this review was to identify occupational health and safety outcomes among sanitary workers worldwide.: PRISMA was used as flow diagram and PICOS was used review questions. The studies published in English were searched from databases and others methods ranging from 2000 to 2022. Boolean logic (AND, OR), MeSH, and keywords used: (Occupation *OR Job *OR Work) AND (Occupational related respiratory Symptoms *OR Disease) AND (Solid waste collectors [SWCs] *OR Street sweepers [SS] *OR Sewage workers and waste treatment [STWs] AND (Countries).Results: A total of 228 studies were identified from 23 countries across the world. Studies were found via PubMed (n=40), Medline (n=25), Embase (n=11) and Global Health (n=66) and Google scholar (n=63) and from previous (n=23). From 8,962 of eligible sanitary workers, about 4742(54 %), 1714(19%) and 1441 (16%) were sewage, sweepers and solid waste workers, respectively. A total study (N=51) were eligible for occupational health and safety outcomes. Of these, respiratory problems accounted 27 (52%) and Gastroenteritis 14 (27%).Despite a large number of studies to date provides sanitary employees all over the world face occupational-related risks, hence more research is needed to enhance and quantify illness burden among sanitary workers.